Pembentukan Portofolio Optimal Saham Jakarta Islamic Index Menggunakan Model Indeks Tunggal - Diyah Novitasari; Titing Suharti; Diah Yudhawati (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
The purpose of this study is to determine the shares of companies listed on the Jakarta Islamic index for the period January 2021 - December 2022 that can form an optimal portfolio. The population in this study were 30 stocks with sample selection using purposive sampling with the criteria that they were consistently listed on the Jakarta Islamic Index during the research period and did not conduct stock spilt during the research period so that 18 stocks were obtained as samples. The analysis technique uses the Single Index Model. The results showed that of the 18 samples, only 4 stocks were included in the optimal portfolio, namely Kalbe Farma Tbk (KLBF) with a fund proportion of 55.23%, Adaro Energy Tbk (ADRO) with a fund proportion of 28.85%, Vale Indonesia Tbk (INCO) with a fund proportion of 9.76% and Bukit Asam Coal Mine Tbk (PTBA) with a fund proportion of 6.16%. This portfolio provides an expected return of 2.62% and a risk of 0.00131%.